Eastern European Countries and the EMU: departure situation and transition strategies. - Joan Costa Font; Joan Batalla Bejerano (European Regional Science Association (ERSA), 1998)
The large amount of literatuture wihin the EMU makes compleatly imposible in one paper to analyze the consequences of the creation of a "monetary zone " in Europe. However, the recent decision of the European Council to incorporate in two phases the most of Eastern European Countires, introduces an interessant issue in order to evaluate the effects in terms of stability, future, dimension and optimality of a EMU based on 21 states. The paper starts explaining the baseic advances of the EMU, introducing some general data of the countries that are suposed to enter in future. As a second part of the paper the basic points of the Optimum Currency Areas will be established, and finally the third part would be an analysis of the future structure of the EMU using the OCA theory and and empirical analysis.
Keywords: 330